Isolasi dan Identifikasi Molekuler Bakteri Asam Laktat pada Dadih dengan Menggunakan Gen 16S rRNA - Alfina Yuliana; Minda Azhar (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Dadih is a food product that is naturally fermented from buffalo milk which contains lactid acid bacteria. Determination of the genus or species of bacteria can be identified molecularly. Bacteria can be identified by phenotype and genotype. This study aims to determine the genus or species of lactic acid bacteria in dadih. Identification of lactic acid bacteria was carried out by isolating lactic acid bacteria from the dadih, then isolating the chromosomal DNA of bacterial isolate that had been obtained. Gene of 16S rRNA was amplificated using the Polymerase Chain Reaction (PCR) method with forward BactF1 and reverse UniB1 primers. The PCR amplicon was sequenced using the Dideoxy-Sanger method with a forward BactF1 primer. Sequencing data was read with the BioEdit program. The size of the 16S rRNA gene fragment obtained was 1040 bp. Analysis of the nucleotide base sequence of the 16S rRNA gene fragment showed that the isolate UBC-DTK-02 belonged to the Enterococcus genus and Enterococcus faecalis spesies.